Implementation of the Restorative Approach in Traffic Accident Cases by the Indonesian Prosecutor's Office - Imaduddin Bagassalam; Harmono Harmono; Dadan Taufik Fathurohman (Jurnal Legisci, 2026)
Background. Traffic accidents are a form of criminal acts that occur quite often in the community and often have a significant impact, both in terms of physical, psychological, and social. Although the perpetrator may not be motivated by intent, they may still be subject to legal sanctions under applicable regulations. To achieve a fairer, more humane, and more efficient justice system, the Attorney General's Office of the Republic of Indonesia issued Regulation No. 15 of 2020 on the Termination of Prosecutions Based on the Principles of Restorative Justice. Aims. The purpose of this study is to analyze the application of restorative justice in traffic accident cases and to evaluate the barriers to its implementation and the factors that support its implementation. Method. The method employed combines a normative and empirical juridical approach, with data collected through literature reviews, interviews, and documentation. Conclusion. The study's findings indicate that the restorative justice approach offers a more peaceful and equitable settlement for all parties involved. However, there remain challenges, including limited understanding among law enforcement officials, low community participation, and weaknesses in oversight mechanisms. Implementation. Therefore, it is necessary to strengthen policies, continue training for prosecutors, and enhance community legal understanding so that restorative justice can be applied optimally and consistently in Indonesia.